2014
DOI: 10.1186/1475-2840-13-43
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vildagliptin, a dipeptidyl peptidase 4 inhibitor, on cardiac hypertrophy induced by chronic beta-adrenergic stimulation in rats

Abstract: BackgroundHeart failure with left ventricular (LV) hypertrophy is often associated with insulin resistance and inflammation. Recent studies have shown that dipeptidyl peptidase 4 (DPP4) inhibitors improve glucose metabolism and inflammatory status. We therefore evaluated whether vildagliptin, a DPP4 inhibitor, prevents LV hypertrophy and improves diastolic function in isoproterenol-treated rats.MethodsMale Wistar rats received vehicle (n = 20), subcutaneous isoproterenol (2.4 mg/kg/day, n = 20) (ISO), subcutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 47 publications
1
37
0
1
Order By: Relevance
“…However, vildagliptin, metformin, and combined metformin and vildagliptin also reduced LDL cholesterol level without any changes in blood pressure. This finding consistent with previous reports in the heart failure model in which vildagliptin did not change blood pressure in rats with cardiac hypertrophy (Miyoshi et al 2014), and metformin did not affect blood pressure and flow-mediated vasodilation in insulin-resistant patients with chronic HF (Wong et al 2012). These data suggest that a reduction of LDL cholesterol level along with lower angiotensin II is necessary to reduce blood pressure in obese-insulinresistant rats with chronic MI.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, vildagliptin, metformin, and combined metformin and vildagliptin also reduced LDL cholesterol level without any changes in blood pressure. This finding consistent with previous reports in the heart failure model in which vildagliptin did not change blood pressure in rats with cardiac hypertrophy (Miyoshi et al 2014), and metformin did not affect blood pressure and flow-mediated vasodilation in insulin-resistant patients with chronic HF (Wong et al 2012). These data suggest that a reduction of LDL cholesterol level along with lower angiotensin II is necessary to reduce blood pressure in obese-insulinresistant rats with chronic MI.…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown to preserve LV function and reduce the infarct size in cardiac I/R injury (Chinda et al 2013, Apaijai et al 2014. Moreover, vildagliptin reduced myocyte hypertrophy and perivascular and cardiac fibrosis in isoproterenol (Miyoshi et al 2014), and transverse aortic constriction-induced heart failure (Takahashi et al 2013). However, inconsistent findings exist as reported by Yin and colleagues who found that vildagliptin did not reverse LV remodeling in post-MI-induced heart failure rats (Yin et al 2011).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Considerable evidence also links the attenuation of DPP4 activity to improvement in ventricular function and reduced systemic and cardiac inflammation (6,(27)(28)(29). Hence, we were surprised to detect increased cardiac expression of mRNA transcripts encoding multiple effectors of the immune response in normoglycemic mice with reduced DPP4 activity.…”
Section: Discussionmentioning
confidence: 93%
“…These effects were accompanied by the amelioration of perivascular fibrosis and expression of genes associated with glucose uptake (GLUT4) and inflammation (TNF α and IL-6) [23]. …”
Section: Cardiovascular Effects Of Dpp-4 Inhibitormentioning
confidence: 99%